Design of a sustainable electric vehicle sharing business model in the Brazilian context - Moro, Suzana Regina; Cauchick-Miguel, Paulo Augusto; Sousa-Zomer, Thayla Tavares de; Sousa Mendes, Glauco Henrique de (International Journal of Industrial Engineering and Management, 2023)
A product-service system (PSS) aims to improve the profitability and competitiveness of companies, generate superior value for customers, and contribute to sustainability. However, despite those benefits, manufacturing companies still find it difficult to structure their business models as PSS, especially regarding the design of sustainable business offers. Previous research on designing PSS business models has not integrated sustainability aspects and empirical evidence on how to design sustainable PSS business models remains limited, especially in contexts such as developing countries, where those offers have a great potential for sustainability improvements. Thus, this paper explores the practical design of a PSS business model for electric vehicle sharing in the Brazilian context, considering sustainable principles. An analysis of the challenges and opportunities of offering shared sustainable mobility in the Brazilian context is presented. The PSS business model is described considering an integrated approach focusing on the co-creation of value-in-use by the value network. The results aim to support practitioners in designing more sustainable PSS business models, generating superior value for the ‘value network’ of PSS and contributing toward expanding sustainable production and consumption knowledge. Article history: Received (September 19, 2022); Revised (April 24 2023); Accepted (May 9, 2023); Published online (May 16, 2023)